The remarkable life of Dr Alexandre Yersin: impact on medical and health development in Vietnam - International Livestock Research Institute (International Livestock Research Institute, 2022)
Dr Alexandre Yersin (1963-1943) was a Swiss-French physician who spent most of his life and work dedicated to Vietnam. He was a world-famous bacteriologist who discovered the origin of the plague in 1894. This report highlights Dr Yersin’s life and accomplishments and discusses lessons learned from his interdisciplinary works to serve communities in Vietnam. We reflect on how his exemplary life can inspire young people, particularly in health research and development.